(3GdJfejI hGdJNda aj GdYGde GdYQHj (B:s (3WQhMGJ JfehjI ddJNda (B/s - (3MjOQ, aDGOs ((3HjQhJ(B: s (3OGQ GdacQ GdYQHj(B, s, 1990)
(3gPG GdcJGH (B1- (3OhQ GdJfejI hGdJNWjW GdGLJeGYj aj GdJZjQ (B2- (3GdJfejI aj GdacQ GdGbJUGOj hGdGLJeGYj (B3- (3GdJfejI hGdHfGA GdGLJeGYj hGdGbJUGOj (B4- (3OhQ GdJNWjW aj GdJfejI GdGbJUGOjI hGdGLJeGYjI NdGUI GdbSe GdChd (B: (3OhQ GdJfejI aj GdJZjQ GdGLJeGYj GdbSe GdKGfj (B: (3GdJfejI hGdJNda aj GdYGde GdYQHj (B1- (3GdScGf hGdJfejI GdGbJUGOjI hGdGLJeGYjI aj GdhWf GdYQHj (B2- (3GdfTGWGJ GdGbJUGOjI GdCSGSjI aj GdhWf GdYQHj (B3- (3GdJHGOd GdOhdj hJCKjQg Ydi GdYGde GdYQHj (B4- (3OhQ Gdbje aj GdJfejI GdGbJUGOjI hGdGLJeGYjI aj GdhWf GdYQHj (B5- (3GdNOeGJ GdGLJeGYjI aj GdYGde GdYQHj (B6- (3GdWQhMGJ GdJfehjI ddJNda aj GdYGde GdYQHjs
Keywords: (3GdJNWjWs; (3GdJNdas; (3GdJfejIs; (3GdYGde YQHjs